A study on factors of internet addiction among degree’s students of FSPPP, UiTM Kedah / Mohd Razman Mohd Zamri, Nurulhasanah Abdul Rahman and Fatin Hazirah Muhd Fadzil - Mohd Zamri, Mohd Razman; Abdul Rahman, Nurulhasanah; Muhd Fadzil, Fatin Hazirah (2012)
The expansion of internet usage has brought along a lot of issues and controversies to the mankind. Some use internet as their medium to release stress, finding source of information, joining social networking and use it on leisure time. There are also several other ways that makes internet use as abusive and harmful to its users. There are a lot of factors that contribute to internet addiction such as the demographic factors, purpose of using internet, the gratification of the use and the frequency of internet usage. The study on the factors will help to see the patterns of internet usage as well as the contributing factors to internet addiction. Therefore, this research aims to know the factors of internet addiction among students in UiTM Kedah. The objective of this study is to know the demographic factors that influence internet addiction, to know the frequency of internet usage that leads to internet addiction, to know the reason why students choose particular purpose of internet usage that contributes to internet addiction, to know the relationship between the factors of internet usage and internet addiction and to know the impacts of internet addiction towards students. The scope of this study covers the Degree students of Faculty of Administrative Science and Policy Studies (FSPPP) UiTM Kedah according to semester, from semester 1 to semester 6. The significance of this study is including that internet plays important roles in students’ life. This study can show the extent to which internet has introduced advantages and disadvantages to its users, more than a decade has passed since the development of the internet. Although a lot of research have been done, it is not sufficient to highlight the factors of internet addiction. It will be great interest to the students to know the factors so that they can use the internet wisely and will provide a basis for improvement in using the internet to ensure that internet addiction can be avoided. The population is all students of Bachelor of Administrative Science from semester 1 to semester 6 of UiTM Kedah.